Gut Microbiome Changes in Patients with Active Left-Sided Ulcerative Colitis after Fecal Microbiome Transplantation and Topical 5-aminosalicylic Acid Therapy - Schierová, Dagmar; Březina, Jan; Mrázek, Jakub; Fliegerová, Kateřina Olša; Kvasnová, Simona; Bajer, Lukáš; Drastich, Pavel (Cells, 2020)
Ulcerative colitis (UC) is an inflammatory bowel disease, and intestinal bacteria are implicated in the pathogenesis of this disorder. The administration of aminosalicylates (5-ASA) is a conventional treatment that targets the mucosa, while fecal microbial transplantation (FMT) is a novel treatment that directly targets the gut microbiota. The aim of this study was to identify changes in fecal bacterial composition after both types of treatments and evaluate clinical responses. Sixteen patients with active left-sided UC underwent enema treatment using 5-ASA (n = 8) or FMT (n = 8) with a stool from a single donor. Fecal microbiota were analyzed by 16S rDNA high-throughput sequencing, and clinical indices were used to assess the efficacy of treatments. 5-ASA therapy resulted in clinical remission in 50% (4/8) of patients, but no correlation with changes in fecal bacteria was observed. In FMT, remission was achieved in 37.5% (3/8) of patients and was associated with a significantly increased relative abundance of the families Lachnospiraceae, Ruminococcaceae, and Clostridiaceae of the phylum Firmicutes, and Bifidobacteriaceae and Coriobacteriaceae of the phylum Actinobacteria. At the genus level, Faecalibacterium, Blautia, Coriobacteria, Collinsela, Slackia, and Bifidobacterium were significantly more frequent in patients who reached clinical remission. However, the increased abundance of beneficial taxa was not a sufficient factor to achieve clinical improvement in all UC patients. Nevertheless, our preliminary results indicate that FMT as non-drug-using method is thought to be a promising treatment for UC patients.
Keywords: dospělí; dárci tkání; biodiverzita; Female; feces; Feces; 5-ASA; Adult; ženské pohlaví; Gastrointestinal Microbiome; Tissue Donors; lidé; fecal microbiome transplantation; Colitis, Ulcerative; Middle Aged; fekální transplantace; diskriminační analýza; Fecal Microbiota Transplantation; microbiome; Administration, Topical; Male; aplikace lokální; Bacteria; střevní mikroflóra; Aged; Discriminant Analysis; ulcerózní kolitida; Biodiversity; Principal Component Analysis; lidé středního věku; mesalamin; senioři; mužské pohlaví; analýza hlavních komponent; ulcerative colitis; Mesalamine; Humans